Yeast fungi as promising agents for biocontrol of mycopathogens in grapes - Volynchuk, Natalia N.; Kabashnikova, Lyudmila F. (Experimental Biology and Biotechnology, 2023)
From the episphere and endosphere of various organs of cultivated grapes (Vitis vinifera L.) variety Alpha, 77 strains of yeast fungi were isolated, of which 6 strains after secondary screening showed antagonistic activity against postharvest mycopathogens of grapes Botrytis cinerea BIM F-71 and Fusarium oxysporum BIM F-609G. The average rate of inhibition of the mycelium of B. cinerea BIM F-71 by native yeast bioagents was 75.1 %, the average rate of inhibition of the mycelium of F. oxysporum BIM F-609G – 65.3 %. Analysis of the minimum inhibitory concentration showed that the concentration of 105 CFU/mL is sufficient to reduce the development of both pathogens by all yeast strains. Of the studied mechanisms of the antagonistic action of yeast fungi, there was a synthesis of urease, cellulase, amylase and partially protease. Production of volatile organic compounds by non-filamentous fungi against B. cinerea BIM F-71 and F. oxysporum BIM F-609G was not revealed.
Keywords: grapes; Botrytis; Fusarium; yeast fungi; biocontrol